2006
DOI: 10.1534/genetics.106.059030
|View full text |Cite
|
Sign up to set email alerts
|

Amh and Dmrta2 Genes Map to Tilapia (Oreochromis spp.) Linkage Group 23 Within Quantitative Trait Locus Regions for Sex Determination

Abstract: Recent studies have revealed that the major genes of the mammalian sex determination pathway are also involved in sex determination of fish. Several studies have reported QTL in various species and strains of tilapia, regions contributing to sex determination have been identified on linkage groups 1, 3, and 23. Genes contributing to sex-specific mortality have been detected on linkage groups 2, 6, and 23. To test whether the same genes might control sex determination in mammals and fishes, we mapped 11 genes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 75 publications
(71 reference statements)
6
99
0
Order By: Relevance
“…Nevertheless, turbot LG5 markers could be indirectly linked to the Oreochromis spp. LG23, where a sexassociated QTL was detected (Shirak et al 2006) from a previous comparative homology demonstrated between Oreochromis spp. LG23 and stickleback LG8 (Sarropoulou et al 2008).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, turbot LG5 markers could be indirectly linked to the Oreochromis spp. LG23, where a sexassociated QTL was detected (Shirak et al 2006) from a previous comparative homology demonstrated between Oreochromis spp. LG23 and stickleback LG8 (Sarropoulou et al 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Also, microarrays constructed from gonadal ESTs have been applied to detect differentially expressed genes in the process of gonadal differentiation (Baron et al 2005). Further, the increased genomic resources in model and aquaculture species have allowed the development of both comparative genomics (Woram et al 2003;Kikuchi et al 2007;Tripathi et al 2009) and candidate gene (Shirak et al 2006;Alfaqih et al 2009) strategies to identify and characterize the SD region in fish. This has permitted the identification of the SD region in eight fish, including both model and aquaculture species (reviewed in Penman and Piferrer 2008).…”
mentioning
confidence: 99%
“…In addition, two potential SD genes, amh and dmrta2, were mapped to the sex-determination loci in ZZ/ZW type turbot (Scophthalmus maximus) and tilapia by applying sex-associated markers and QTL analysis [142,143]. Xu et al [144] also observed regulative role of dmrta2 in zebrafish spermatogenesis.…”
Section: Sex-determining Genes In Fish With Zz/zw Sex Determination Smentioning
confidence: 99%
“…Genetic maps are thus needed and will allow the mapping of loci underlying quantitative variation (quantitative trait loci (QTL); Lander & Botstein 1989;Leder et al 2006;Shirak et al 2006), map-based cloning of genes defined by mutant or natural alleles (Karsi & Waldbieser 2004;Kazianis et al 2004b) and comprehensive investigation of genome evolution between related strains and species (Gates et al 1999;Naruse et al 2000;Danzmann et al 2005;Stemshorn et al 2005).…”
Section: Introductionmentioning
confidence: 99%